Increased nitrogen fertilization inhibits the biocontrol activity promoted by the intercropping partner plant. (25th July 2020) - Wang, Leyun; Cui, Hongying; Chang, Xinyue; Zhu, Mengmeng; Zhao, Zihua
Abstract: The examination of the compatibility between agricultural practices and biocontrol activities is crucial for establishing an efficient, eco‐friendly, and sustainable pest management program. In this study, we examined the population dynamics of two specialist aphids, the English grain aphid ( Sitobion avenae ) on potted wheat and the pea aphid ( Acyrthosiphon pisum ) on potted alfalfa, as well as the biocontrol activity of a generalist predator, the harlequin ladybird beetle ( Harmonia axyridis ). We investigated their responses to the presence of the intercropping partner plant species (alfalfa and wheat, respectively) through plant volatiles or visual cues at three nitrogen fertilizer levels in a greenhouse. In the absence of the predator, the English grain aphid population growth rate increased significantly with increasing nitrogen levels, whereas the pea aphid population increased significantly more slowly in response to high nitrogen levels. The English grain aphid and pea aphid population dynamics were unaffected by the presence of the intercropping partner. However, the presence of the intercropping partner enhanced the control of both aphid populations by the harlequin ladybird beetle. Increasing nitrogen fertilizer levels decreased the predation rates, which were otherwise increased by the intercropping partner. The beneficial effects of the intercropping partner were eventually non‐existent at the highest nitrogen level tested. These results imply that the interaction between the presence of intercropping partner and the nitrogen fertilizer application affects the biocontrol activity of the natural enemies of insect pests. Thus, the compatibility between agricultural intensification and biocontrol strategies in integrated pest management programs need to be investigated. Abstract : The examination of the compatibility between agricultural practices and biocontrol activities is crucial for establishing an efficient, eco‐friendly, and sustainable pest management program. In this study, we examined the population dynamics of two specialist aphids, the English grain aphid ( Sitobion avenae ) on potted wheat and the pea aphid ( Acyrthosiphon pisum ) on potted alfalfa, as well as the biocontrol activity of a generalist predator, the harlequin ladybird beetle ( Harmonia axyridis ). We investigated their responses to the presence of the intercropping partner plant species (alfalfa and wheat, respectively) through plant volatiles or visual cues at three nitrogen fertilizer levels in a greenhouse. In the absence of the predator, the English grain aphid population growth rate increased significantly with increasing nitrogen levels, whereas the pea aphid population increased significantly more slowly in response to high nitrogen levels. The English grain aphid and pea aphid population dynamics were unaffected by the presence of the intercropping partner. However, the presence of the intercropping partner enhanced the control of both aphid populations by the harlequin ladybird beetle. Increasing nitrogen fertilizer levels decreased the predation rates, which were otherwise increased by the intercropping partner. The beneficial effects of the intercropping partner were eventually non‐existent at the highest nitrogen level tested. These results imply that the interaction between the presence of intercropping partner and the nitrogen fertilizer application affects the biocontrol activity of the natural enemies of insect pests. Thus, the compatibility between agricultural intensification and biocontrol strategies in integrated pest management programs need to be investigated.